Modeling lineage and phenotypic diversification in the New World monkey (Platyrrhini, Primates) radiation - Arístide, Leandro (2013)
Adaptive radiations that have taken place in the distant past can now be more thoroughly studied with the availability of large molecular phylogenies and comparative data drawn from extant and fossil species. Platyrrhines are a good example of a major mammalian evolutionary radiation confined to a single continent, involving a relatively large temporal scale and documented by a relatively small but informative fossil record. Here, we present comparative evidence using data on extant and fossil species to explore alternative evolutionary models in an effort to better understand the process of platyrrhine lineage and phenotypic diversification. Specifically, we compare the likelihood of null models of lineage and phenotypic diversification versus various models of adaptive evolution. Moreover, we statistically explore the main ecological dimension behind the platyrrhine diversification. Contrary to the previous proposals, our study did not find evidence of a rapid lineage accumulation in the phylogenetic tree of extant platyrrhine species. However, the fossil-based diversity curve seems to show a slowdown in diversification rates toward present times. This also suggests an early high rate of extinction among lineages within crown Platyrrhini. Finally, our analyses support the hypothesis that the platyrrhine phenotypic diversification appears to be characterized by an early and profound differentiation in body size related to a multidimensional niche model, followed by little subsequent change (i.e., stasis).